PEMETAAN KUALITAS PERMUKIMAN DI KECAMATAN GUGUAK PANJANG KOTA BUKITTINGGI MENGGUNAKAN CITRA QUICKBIRD - Yoga Algery; Endah Purwaningsih (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
The research purpose is to get information about : 1) The parameters of settlementsquality, 2) the distribution of settlement quality in Guguak Panjang District and 3) theleel of accuracy of Quickbird imagery interpretation. The method used are scorring and overlay on each parameter to determine settlement quality.The Image accuracy test uses the Confution Matrix method. Based on the resultof the study 1) The parameters of settlements quaity include residential building density, the layout of building, the width of the settlement entrance, the condition of residential roads, settlements location, floods, the waste and drainage system, obtained three classes of settlement quality: good settlement quality covering 18,9 Ha, medium settlements quality is 119,3 Ha and poor settlement quality is 0,5 Ha, 2) The distributons of the highest good settlemets quality is in Bukit Apit Puhun Village with 7,7 Ha, the highest medium settlements quality is in Tarok Dipo Village with 37,9 Ha and poor settlements quality is in Tarok Dipo Village area 0,5 Ha, 3) The Image accuracy test produces an accuracy value of 94,4%.